2015
DOI: 10.1371/journal.pone.0120420
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Aβ Oligomer IgG and Surface Sialic Acid in Intravenous Immunoglobulin: Measurement and Correlation with Clinical Outcomes in Alzheimer’s Disease Treatment

Abstract: The fraction of IgG antibodies with anti-oligomeric Aβ affinity and surface sialic acid was compared between Octagam and Gammagard intravenous immunoglobulin (IVIG) using two complementary surface plasmon resonance methods. These comparisons were performed to identify if an elevated fraction existed in Gammagard, which reported small putative benefits in a recent Phase III clinical trial for Alzheimer’s Disease. The fraction of anti-oligomeric Aβ IgG was found to be higher in Octagam, for which no cognitive be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 66 publications
(134 reference statements)
6
16
0
Order By: Relevance
“…Both global and local fits were performed. Based on published ELISA results and SPR calibration free concentration analysis [21], the natural Ab + IgG concentration in IVIG used for fitting was 60 nM [8,22].…”
Section: Spr Analysismentioning
confidence: 99%
“…Both global and local fits were performed. Based on published ELISA results and SPR calibration free concentration analysis [21], the natural Ab + IgG concentration in IVIG used for fitting was 60 nM [8,22].…”
Section: Spr Analysismentioning
confidence: 99%
“…This finding is somewhat surprising given that both mAbs 6E10 and 4G8 exhibit a similar affinity towards the same target, although different epitopes and IgG subclasses could explain the difference [46]. A subsequent investigation of 4G8 and 6E10 glycosylation showed that 4G8 and human anti-Aβ IgG exhibited surface accessible sialic acid groups that could be removed with neuraminidase [47]. By contrast, surface sialic acid was largely absent from 6E10 [47].…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent investigation of 4G8 and 6E10 glycosylation showed that 4G8 and human anti-Aβ IgG exhibited surface accessible sialic acid groups that could be removed with neuraminidase [47]. By contrast, surface sialic acid was largely absent from 6E10 [47]. Taken together, these studies suggested that surface-accessible sialic acid could play a role in BBB transport kinetics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations